THU0039 B1-Integrin is a Critical Mediator of TLR2-Induced Migrational and Invasive Mechanisms in RA Synovial Fibroblast Cells. (23rd January 2014) - Mcgarry, T.; Fearon, U.; Gao, W.; Jackson, M.; McCormick, J.; Veale, D.; Connolly, M.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic, progressive autoimmune disease, characterized by synovial proliferation and destruction of cartilage and bone. Engagement of integrin receptors induces cell migration/invasion through attachment to the extracellular matrix and downstream activation of RhoGTPases [1 ]. TLR2 has been implicated in the pathogenesis of joint destruction in RA [2 ], however, the mechanisms involved have yet to be elucidated. Objectives: This study investigates the role of β1-integrin in mediating TLR2-induced cytoskeletal rearrangement, cell migration and invasion processes in vivo and in vitro . Methods: β1-integrin expression and cytoskeletal rearrangement were assessed by immunohistochemistry, F-actin immunoflourescent staining and RT-PCR. β1-integrin binding (β1-4, β6, avβ5, a5β1), cytoskeletal rearrangement and RhoGTPase Rac-1 activation in response to Pam3CSK4 (1μg/ml)(TLR2-ligand) in RASFC and HMVEC were assessed by a multiplex adhesion binding assay, F-actin immunofluorescent staining and Rac-1 pull down assays/Western blot. The effect of Pam3CSK4 on cell migration, invasion and Rac-1 activation in the presence of anti-β1-integrin or anti-IgG control was assessed by wound repair assays, ex vivo RA synovial explant matrigel outgrowths, transwell matrigel™ invasion chambers and Rac-1 pulldown/western blot. Results: β1-integrin expression is significantly increased in RA synovial tissue lining layer, sub-lining layer and vasculature in comparison to OA and control tissue (p<0.05). Pam3CSK4 specifically induced β1-integrin binding in RASFC (p<0.05), with no effect observed for β2-4, β6, avβ5 or a5β1 binding. Pam3CSK4 significantly induced β1-integrin mRNA and protein expression in RASFC (p<0.05), and promoted RASFC/HMVEC cytoskeletal disassembly, microspike formation and filopodia extensions. Downstream from β1-intgerin, Pam3CSK4 induced Rac-1 activation, critical for cytoskeletal dynamics and cell motility. Consistent with this Pam3CSK4 induced RASFC/HMVEC migration, invasion, RA synovial explant outgrowths and Rac-1 activation were inhibited in the presence of anti-β1-integrin (p<0.05), with no effect observed for anti-IgG control. Conclusions: TLR2 activation induces migrational and invasive mechanisms through β1-integrin-induced cytoskeletal pathways, processes which are critically involved in the pathogenesis of RA. References: Brakebusch, C., Bouvard, D., Stanchi, F. et al (2002) Integrins in Invasive Growth J Clin Invest. 109:999-1006 Seibl, R., Birchler, T., Loeliger, S. et al (2003) Expression and Regulation of Toll-like Receptor 2 in rheumatoid arthritis synovium. Am J Pathol 162:1221-7 Brentano, F., Kyburz, D., Schorr, O. et al (2005) The role of Toll-like receptor signalling in the pathogenesis of arthritis. Cell Immunol 233:90-6 Disclosure of Interest: T. Mcgarry: None Declared, U. Fearon: None Declared, W. Gao: None Declared, M. Jackson: None Declared, J. McCormick: None Declared, D. Veale Grant/research support from: Abbott, Opsona, Pfizer, Roche, Consultant for: MSD, Pfizer, Roche, Speakers bureau: Janssen, MSD, Pfizer, UCB, M. Connolly: None Declared